Application of Activated Seashells and Sand Armor for Disrupting N and P Release from River Sediments - Quansah, Jude Ofei; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Water (Switzerland), 2022)
We investigated the applicability of oyster (OS) and mussel shells (MS) as capping materials to inhibit the movement of nitrogen (N) and phosphorus (P) from river sediments. OS and MS are difficult to dispose of as waste, and have been used environmentally to clean up sediments contaminated with nitrogen and phosphorus. OS and MS increased the nutrient adsorption efficiency through simple heat treatment. The effectiveness of OS and MS capping with sand armor (SA) was evaluated in laboratory incubation experiments for 63 d. The sediments were capped with an active capping material (OS or MS) and then with either 1 cm or 3 cm SA. The pH and EC values were remarkably high under MS capping conditions because Ca2+ and Mg2+ were eluted from the MS material. The elution of Ca2+ and Mg2+ negatively affected the inhibition of NH4-N release by MS capping. OS capping demonstrated better performance for blocking the release of NH4-N and T-N than that of MS capping; the efficiency was enhanced by adding a 3 cm SA layer on top of the MS layer. In contrast, the PO4-P and T-P releases from the river sediments were effectively impeded by MS capping. OS capping with a 3 cm SA layer (OS/SA3) was recommended as the best capping strategy for inhibiting N and P releases from river sediments. The capping efficiencies of OS/SA3 for NH4-N, T-N, PO4-P, and T-P were 92.2%, 51.4%, 101.3%, and 93.3%, respectively.
Keywords: Adsorption efficiency; Armour layers; Ca 2+; Capping; Capping materials; Mussel shells; Nitrogen and phosphorus; Oyster shell; River sediments; Simple++; capping; mussel shell; nitrogen; oyster shell; phosphorus; sediment